"We are waiting fro mail from France" : Communication and circulation of news in French colonial Africa (19-20th centuries) - (:unkn) unknown (My University, 2018)
This research focuses on the circulation of news in French West Africa in the 19th and 20th centuries, tracing the genesis of communications and the creation of an ad hoc staff. In the framework of the history of communications in a colonial context, we wanted to pay special attention to social actors: individuals who hoped for mail or sent it far away; those who learned how to use mail, telegraph and telephone; and the postal staff (pedestrians, letter carriers, receivers, telegraph operators, etc.) who gradually formed an important and sometimes demanding social group in French Africa.
Keywords: African Research